KONSEP PRODUK TABUNGAN PADA BANK SYARIAH (Produk Tabungan Wadi’ah dan Mudharabah) - Nursalim, Eko (At-Tawazun, Jurnal Ekonomi Syariah, 2021)
Islamic Bank fund collection products include savings, demand deposits and time deposits. In its operations, Islamic Bank has several fund products and services. One of the existing fund products in Syariah Bank is savings. Savings in Islamic Banks there are two contracts namely Mudharabah contract and wadi'ah. Al-wadi'ah is a deposit or deposit in a Islamic bank. The principle of al-wadi'ah is a pure deposit from one party to another party, both individual and legal entity that must be maintained and returned at any time if the cravicant wants. In the wadi'ah contract there is no profit sharing, so only the bonus given by the bank to its customers. Saving with Mudharabah contract is a type of savings that uses a mudharabah contract withdrawal may be made in accordance with the agreement.